Mid Regional Pro-Adrenomedullin, Lactate, and Risk Factors as Predictors of Sepsis Severity - Andi Widagdo, Heribertus; Kurniati, Amiroh; Pramudianti, Maria Immakulata Diah (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2025)
Sepsis is a syndrome determined by pathogenic and host factors, including gender, age, comorbidities, and bacteremia. A high level of MR pro-ADM is associated with vascular relaxation, while a high lactate level indicates tissue hypoxia and anaerobic metabolism. This study aimed to assess MR pro-ADM and lactate as predictors of sepsis severity by considering age, gender, comorbidities, clinical screening, and bacterial culture result factors. This study used an observational analytic research design with a prospective cohort approach. Researchers consecutively collected a sample of 80 sepsis patients at Dr. Moewardi Regional General Hospital (RSDM) in February-March 2023. Clinical characteristics, demographics, physical examinations, and laboratory results were collected from medical records and the Hospital Information System (HIS) of RSDM. MR pro-ADM and lactate levels were measured by Enzyme-Linked Immunosorbent Assay (ELISA) and enzymatic amperometric methods. There were significant differences in severity and mortality predictor variables (clinical screening, log_lactate >0.40, bacterial culture). The ranking of the strength of association of predictors of severity was clinical screening ((Odds Ratio (OR)=15.40), bacterial culture results (OR=3.7), log_lactate (OR=2.74). Clinical screening, lactate, and culture results were independent predictors of sepsis severity. Multi-center studies with more complete data, considering other factors that influence sepsis, and using more accurate methods of measuring ADM and lactate are recommended.